2012
DOI: 10.1007/s10787-011-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs in the treatment and/or prevention of neurological disorders

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) have been used extensively in the treatment of inflammatory disorders and pain. In recent years, emerging data suggest that some NSAIDs possess pharmacological properties, in addition to cyclooxygenase inhibition, which may be beneficial in the treatment of several neurological conditions. For example, fenamate NSAIDs potentiate GABA-A receptor function, indomethacin scavenges nitric oxide free radicals, and acetylsalicylic acid inhibits the translocation of NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Extensive knowledge of ion channels targeted by FFA may revive interest in the use of this molecule for therapeutic purposes, as was suggested for NSAIDs, especially fenamates, in the treatment of neurological disorders (Khansari & Coyne, 2012). The recently developed FFA hydrophobic derivative nanoprodrugs show an increase in the drug efficiency (Lee et al ., 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive knowledge of ion channels targeted by FFA may revive interest in the use of this molecule for therapeutic purposes, as was suggested for NSAIDs, especially fenamates, in the treatment of neurological disorders (Khansari & Coyne, 2012). The recently developed FFA hydrophobic derivative nanoprodrugs show an increase in the drug efficiency (Lee et al ., 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies also indicate that chronic use of non-steroidal anti-inflammatory drugs (NSAIDs) reduces the risk of developing AD in normal aging populations [ 6 , 7 ]. A primary action of NSAIDs is enzymatic inhibition of cyclooxygenases (COX)-1 and COX-2 activity which further leads to an inhibition of downstream prostaglandin signaling and also exerts multiple adverse side effects mainly characterized by gastrointestinal bleeding and cardiovascular events [ 8 , 9 ]. In prostaglandin (PG) signaling pathway, tissue-specific terminal prostaglandin synthases or isomerases convert PGH2 into biologically active prostaglandins (PGs), namely, PGD2, PGE2, PGF2a, and PGI2 (also known as prostacyclin), as well as thromboxane A2 (TxA2) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…tients [12, 13, 28, 29]. Epidemiological studies have shown that NSAIDs act distinctly in different stages of AD.…”
Section: Discussionmentioning
confidence: 99%
“…However, many experiments found that although sustained administration of selective COX-2 inhibitor could prevent mild cognitive impairment caused by acute or chronic brain injury disease, it could not heal severe AD patients or reverse their cognitive defects. Additionally, the long-term use of these drugs increase the risk of bleeding, gastrointestinal ulcers, fatal heart and cerebrovascular side effects [12, 13]. Therefore, it was suggested that COX-2 downstream signaling needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation